The philosophy of thomas kuhn: paradigms and scientific revolutions in islamic scholarship - Muhamad Fadli; Diana Monita; Muhammad Chafidz Ali Wafa (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
One of the figures who strongly criticized positivism was Thomas Kuhn. Kuhn criticizes the opinion of positivism which says that science develops cumulatively and evolutionarily. This is then refuted by Kuhn by presenting the concept of scientific paradigm and revolution. The author tries to see the concept of paradigm and scientific revolution in the body of Islamic scholarship. The author uses the library research method in conducting this research. While in collecting data related to the topic discussed by the author using documentation techniques. The results of this study state that the development of science is continuous or can be called continuously evolving. In the course of its evolution, science will experience an old paradigm or a normal phase of science, then enter a period of anomaly and crisis. The end of this cycle is the formation of a new normal science or the birth of a new paradigm. If Thomas Kuhn's thoughts are brought into the context of Islamic scholarship, then at this time it is at the anomaly stage, namely the many differences that occur in understanding a problem. But not until entering the crisis stage which requires finding a new paradigm, this is because each opinion has different arguments and understanding.